2015
DOI: 10.1007/s00380-015-0754-1
|View full text |Cite
|
Sign up to set email alerts
|

Use and outcome of thrombus aspiration in patients with primary PCI for acute ST-elevation myocardial infarction: results from the multinational Euro Heart Survey PCI Registry

Abstract: The clinical benefit of thrombus aspiration (TA) in patients presenting with acute ST-elevation myocardial infarction (STEMI) and treated with primary percutaneous coronary intervention (PCI) is not well defined. Furthermore, there is a large variation in the use of TA in real-world registries. Between 2005 and 2008, a total of 7146 consecutive patients with acute STEMI undergoing primary PCI were prospectively enrolled into the PCI Registry of the Euro Heart Survey Programme. For the present analysis, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…A recent meta-analysis of randomised trials reporting mortality as a primary outcome (either all-cause or cardiovascular) similarly concluded that, contrary to the expectations of many interventionalists, TA with PCI does not reduce the rates of death, nor secondary endpoints, such as reinfarction, stent thrombosis or stroke. 19 Furthermore, our data extend registry data from STEMI patients 20,21 to patients with NSTEMI/STEMI.…”
Section: Discussionsupporting
confidence: 62%
“…A recent meta-analysis of randomised trials reporting mortality as a primary outcome (either all-cause or cardiovascular) similarly concluded that, contrary to the expectations of many interventionalists, TA with PCI does not reduce the rates of death, nor secondary endpoints, such as reinfarction, stent thrombosis or stroke. 19 Furthermore, our data extend registry data from STEMI patients 20,21 to patients with NSTEMI/STEMI.…”
Section: Discussionsupporting
confidence: 62%
“…With the aggravation of aging, the improvement of people’s living standard and the change of life style, the incidence of coronary atherosclerotic heart disease is increasing year by year, and the age of patients becomes younger 3,4. At present, the most effective treatment for acute myocardial infarction is percutaneous coronary intervention (PCI), which can effectively relieve the clinical symptoms of patients 5,6. However, a large number of studies have shown that patients with acute myocardial infarction are prone to re-thrombosis or vascular stenosis after receiving PCI 7,8.…”
Section: Introductionmentioning
confidence: 99%
“…Em comparação com períodos anteriores, P3 apresentava maior prevalência de trombo visível à angiografia (76,6% vs. 88,8% vs. 92,3%; p<0,001), com queda no uso adjunto de 15 enquanto que no registro europeu Euro Heart Survey PCI Registry, compreendendo dados coletados de 33 países da União Europeia, a utilização do AMT ocorreu em 12,6% das ICP primárias − taxa mais próxima da de nosso registro. 16 A CENIC não foi concebida especificamente para a análise do uso de ATM, e dados relacionados às circunstâncias de seu emprego não foram coletados. Assim, especulam-se, como possíveis razões para sua baixa utilização, aquelas relacionadas ao médico, como difusão da nova tecnologia, internalização e implementação do uso, ou relacionadas ao sistema, como reembolso e limitação dos recursos do sistema de saúde brasileiro.…”
Section: Resultsunclassified